The Evaluation of Psychosocial Risks: An Emerging Issue? And its Prevention... A Postponed Issue? - Cunha, Liliana; Barros, Carla (Journal of Tourism, Sustainability and Well-being, 2018)
Psychosocial risks, its diagnosis and better understanding, have, in recent years, occupied a central place in the societal debates, setting new demanding to the ones involved in the field of occupational safety and health. In line with this, the concerns of evaluation and diagnosis of psychosocial risk factors boosted the development of several questionnaires, their widespread dissemination, and even their “exportation”, not always sensitive to the specificities of local realities. The purpose of this paper is to discuss the methods of “diagnosis” and the type of prevention practices, taking into account the comparison of two surveys in this area and the theoretical and epistemological approaches that underlie them: (i) the Copenhagen Psychosocial Questionnaire (COPSOQ) and (ii) the Health and Work Survey (INSAT). The results reinforce the importance of a contextualized approach in work situations, as well as in the perspective of the workers themselves about the risks to which they are exposed to - beyond what is, or not, significant from the statistical point of view, or what can be normatively defined as an “acceptable risk”.